A prognostic model in patients with advanced biliary tract cancer receiving first-line chemotherapy. (3rd October 2021) - Filippi, Roberto; Montagnani, Francesco; Lombardi, Pasquale; Fornaro, Lorenzo; Aprile, Giuseppe; Casadei-Gardini, Andrea; Faloppi, Luca; Palloni, Andrea; Satolli, Maria Antonietta; Scartozzi, Mario; Citarella, Fabrizio; Lutrino, Stefania Eufemia; et al.
Abstract: Background: Standard treatment of advanced biliary tract cancer (aBTC) is represented by first-line chemotherapy (CT1). However, some patients do not gain any benefit from CT1, contributing to the overall dismal prognosis of aBTC. The present study aimed to devise a prognostic model in aBTC patients receiving CT1. Methods: A large panel of clinical, laboratory, and pathology variables, available before the start of CT1, were retrospectively assessed in a multi-centric cohort to determine their prognostic value on univariate and multivariate regression analysis. The variables that showed a significant correlation with overall survival (OS) were computed in a three-tier prognostic score. External validation of the prognostication performance was carried out. Results: Clinical histories of 935 patients (median OS 10.3 months), with diagnosis dates ranging from 2001 to 2017, were retrieved from 14 institutions. According to multivariate analysis, Eastern Cooperative Oncology Group performance status, carbohydrate antigen 19.9, albumin levels, and neutrophil/lymphocyte ratio were strongly associated with OS ( p  <0.01). The prognostic score could generate a highly significant stratification (all between-group p values ≤0.001) into groups of favorable (comprising 51.5% of the sample), intermediate (39.2%), and poor prognosis (9.3%): median OS was 12.7 (CI95% 11.0–14.4), 7.1 (CI95% 5.8–8.4), and 3.2 months (CI95% 1.7–4.7), respectively. This OS gradient was replicated in the validation set (129 patients), with median OS of 12.7 (CI95% 11.0–14.3), 7.5 (CI95% 6.1–8.9), and 1.4 months (CI95% 0.1–2.7), respectively (all between-group p values ≤0.05). Conclusion: A prognostic score, derived from a limited set of easily-retrievable variables, efficiently stratified a large population of unselected aBTC patients undergoing CT1. This tool could be useful to clinicians, to ascertain the potential benefit from CT1 at the start of treatment.